Tactile System for Visually Impaired People Using Embedded Technology - G.Theivanathan; A.Mohamed Sikkander; N.Hemavathy; Murukesh; Sangeeta R. Mishra (International Journal of Scientific Research and Innovative Studies, 2022)
People who are visually handicapped or blind rely on others to get from one place to another. In metropolitan settings, various systems are utilized to tell blind people of the direction of their travel. The majority of navigation systems dedicated to guiding the blind are voice-based. However, due to the tremendous noise produced by heavy traffic in urban locations, voice information is unreliable. It drastically reduces perception of commands generated by the blind person's ear buds. This study describes the invention of a vibrotactile approach for guiding a visually impaired person in metropolitan environments. It is a straightforward and successful strategy. It is made up of soft wovibrators that are placed on the left and right arms of their shoulders and produce vibrations by hapticperception, which is specifically produced by regulated hardware and software. Even in heavy traffic, the blind person can quickly identify the safe path on a walk using touch sensing. This tactile technology largely overcomes the shortcomings of the voice-based approach.